2020
DOI: 10.4018/978-1-7998-2372-8.ch005
|View full text |Cite
|
Sign up to set email alerts
|

Forging University Social Responsibility Through Community Engagement at Higher Education

Abstract: This chapter interrogates the notion of community engagement or service learning. The chapter argues that universities pay lip service to community engagement to the detriment of teaching and research functionaries. Most prestige universities operate on the belief that it is only research that matters; hence, research is prioritized. Universities and their staff have adopted an ‘ivory tower' attitude. This modus operandi negates the reality that reliable knowledge could be produced through responsible communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The study's findings revealed that while the needs of the community within which the university is located attractive sites for community-gown projects, the challenge of accessing some of these sites made it difficult for the institution of community development projects. Although Murphy and McGrath (2018) reveal that community engagement is more important and impactful when done in rural areas where development is much-needed, the findings of this study are corroborated by Tshishonga (2020), who reveals that the experiences of academics and students involved in community development projects are often frustrating and disheartening because of factors that are beyond the influence of the academic institutions. The findings of this study correlate with previous studies that reveal that in some instances, despite the appetite that universities can have to implement community engagement projects, the inability to reach such communities often kills the drive for community engagement projects (Akib et al 2017;Johnson 2017;Stepanek-Lockhart 2018).…”
Section: Community Accessibility Issuesmentioning
confidence: 51%
“…The study's findings revealed that while the needs of the community within which the university is located attractive sites for community-gown projects, the challenge of accessing some of these sites made it difficult for the institution of community development projects. Although Murphy and McGrath (2018) reveal that community engagement is more important and impactful when done in rural areas where development is much-needed, the findings of this study are corroborated by Tshishonga (2020), who reveals that the experiences of academics and students involved in community development projects are often frustrating and disheartening because of factors that are beyond the influence of the academic institutions. The findings of this study correlate with previous studies that reveal that in some instances, despite the appetite that universities can have to implement community engagement projects, the inability to reach such communities often kills the drive for community engagement projects (Akib et al 2017;Johnson 2017;Stepanek-Lockhart 2018).…”
Section: Community Accessibility Issuesmentioning
confidence: 51%
“…To facilitate the process, it is suggested that the procedure surrounding the necessary paperwork, such as the MOU or ethics clearance, be moderated, so that students and researchers may find it easier to carry out important work with their communities (Jansen, 2010). MOU helps to balance the key functions and provides enormous expectations in university education, especially in relation to up-skilling and further provision of solutions to challenges facing contemporary society (Tshishonga, 2020).…”
Section: The Community In Relation To Hementioning
confidence: 99%